Pentingnya Penggunaan Bahasa yang Berbudaya sebagai Gaya Komunikasi Siswa pada Era Digital di MTsN 1 Kota Serang - Rizky Nur Pratama; Sri Khaerunnisa; Nazwa Sabrina Fatihah; Aditya Maulana; Iin Hindayati; Rina Andriani (Pusat riset dan Inovasi Nasional, 2025)
This study aims to examine the importance of using cultural language as a communication style for students in the digital era at MTsN 1 Kota Serang. The rapid development of digital technology affects the way they communicate, including among students. The use of language that is not in accordance with cultural rules is often found in online interactions, which has the potential to damage cultural values and social norms. Therefore, it is important to instill an understanding of the importance of cultural language as part of students' identity and character. This study uses a qualitative approach with interview and observation methods to explore the views of students, teachers, and parents regarding the application of cultural language in digital communication. The results of the study show that although students are accustomed to using digital technology, they still need to be given a deeper understanding of the use of language that is in accordance with local culture and applicable norms. It is hoped that the results of this study can be the basis for designing a cultural language education program in the curriculum, as well as increasing students' awareness of the importance of communicating politely and ethically in the digital world. This study also provides recommendations for schools in facilitating cultural language learning as part of student character formation.